Macrofaune Restoration In Peat One Year After Burning - Muhamad Habibi Rachman; Adiwirman Adiwirman; Wawan Wawan (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2021)
Macrofauna data on post-fire peat soils have been documented in many literatures, but assessments of soil macrofauna recovery in peatlands after one and a half years after fires are scarce. The aim of this study was to evaluate the recovery of soil macrofauna in peatlands after one and a half years after fires. This research was conducted on peat land in PT.SSS Kuala Panduk Teluk Meranti District, Pelalawan Regency. This research was conducted by survey method. Determination of the location using the purposive sampling method, especially on peatlands after one and a half years after the fire and unburned peatlands. Based on peatland cover, 6 samples were taken, and 6 samples were taken from unburned peatland. Determination of the sampling point using a systematic method. Macrofauna observations included number of families, number of individuals, population density, and diversity index. The study of macrofauna recovery was carried out by t-test on macrofauna data on peatland fires and unburned peatlands. The results shown in peatlands after a year and a half of fires are macrofauna recovery.